Analisis Kelayakan Ekowisata Wisata Alam Danau Sigombak Desa Teluk Kembang Jambu Kabupaten Tebo Provinsi Jambi: Feasibility Analysis of Natural Tourism Sigombak Lake Teluk Kembang Jambu Village Tebo Districy Jambi Province - Rahmad, Rahmad Nurmansah; Fazriyas, Fazriyas; Rosanti, Elda (Jurnal Silva Tropika, 2022)
ABSTRACT Ecotourism is a tourist trip to areas where the natural environment is still pristine by respecting their cultural and natural heritage. Lake Sigombak Nature Tourism is located in Teluk Kembang Jambu Village, Tebo Regency, and has a natural tourist attraction in the form of a lake with an island in the middle but it also has a cultural tourism attraction. Lake Sigombak Tourism Management cannot be separated from the lack of coordination from related stakeholders, so that the development plan and management of Lake Sigombak tourism cannot be carried out properly, it is necessary to conduct research on Feasibility Analysis of Ecotourism for Lake Sigombak Nature Tourism. This type of research is descriptive qualitative which was conducted for one month, in Teluk Kembang Jambu Village, Tebo Regency. Data collection techniques were carried out by direct observation, interviews, and documentation. The sample of this research is the visitors of Lake Sigombak Nature Tourism taken by using the Accidental Sampling method. Data analysis used descriptive qualitative techniques. Based on the results of research based on ODTWA, the Lake Sigombak Nature Tourism Area got an average index value of 64.64% of the average overall criteria. Attractiveness gets a score of 64.15%. Accessibility scored 67.86%, accommodation 33.33%, supporting facilities and infrastructure 87.93%, conditions around the area scored 65.09%, water and environmental conditions 82.99%, and marketing 51.15%. Overall, the Lake Sigombak Ecotourism area is declared unfit for development, so there is still a lot that needs to be improved, seeing the tourism conditions found in the Lake Sigombak Nature Tourism area. Keywords: Ecotourism, Lake Sigombak Nature Tourism, Natural Tourism Attractions (NTA).   ABSTRAK Ekowisata adalah perjalanan wisata ke wilayah-wilayah yang lingkungan alamnya masih asli dengan menghargai warisan budaya dan alamnya. Wisata Alam Danau Sigombak terletak di Desa Teluk Kembang, Jambu, Kabupaten Tebo, dan memiliki daya tarik wisata alam berbentuk Danau dengan Pulau ditengahnya selain itu juga memiliki daya tarik Wisata Budaya. Pengelolaan Wisata Danau Sigombak tak lepas dari kurangnya kordinasi dari stake holder terkait, sehingga rencana pembangunan dan pengelolaan wisata Danau Sigombak tidak mampu terlaksana dengan baik, maka perlu dilakukan penelitian mengenai Analisis Kelayakan Ekowisata Wisata Alam Danau Sigombak. Jenis penelitian ini adalah Kualitatif Deskriftif yang dilakukan selama satu bulan, di Desa Teluk Kembang Jambu, Kabupaten Tebo. Teknik pengambilan data dilakukan dengan Observasi secara Langsung, Wawancara, dan Dokumentasi. Sampel penelitian ini adalah pengunjung Wisata Alam Danau Sigombak yang diambil dengan menggunakan metode Accidental Sampling. Analisis data menggunakan teknik kualitatif deskriftif. Berdasarkan hasil penelitian yang berpedoman pada ODTWA, Kawasan Wisata Alam Danau Sigombak mendapatkan nilai indeks rata rata 64,64% dari rata rata keseluruhan kriteria. Daya tarik mendapatkan nilai sebesar 64,15%. Aksesibilitas mendapatkan nilai sebesar 67,86%, Akomodasi sebesar 33,33%, sarana dan prasarana penunjang sebesar 87,93%, kondisi sekitar kawasan mendapatkan nilai sebesar 65.09%, kondisi air dan lingkungan sebesar 82.99%, dan pemasaran mendapatkan nilai sebesar 51.15%. Secara keseluruhan kawasan Ekowisata Danau Sigombak dinyatakan belum layak dikembangkan, sehingga masih sangat banyak yang perlu diberbaiki, melihat kondisi Wisata yang ditemukan di kawasan Wisata Alam Danau Sigombak. Kata kunci: Ekowisata, Obyek Daya Tarik Wisata Alam (ODTWA), Wisata Alam Danau Sigombak ABSTRACT Ecotourism is a tourist trip to areas where the natural environment is still pristine by respecting their cultural and natural heritage. Lake Sigombak Nature Tourism is located in Teluk Kembang Jambu Village, Tebo Regency, and has a natural tourist attraction in the form of a lake with an island in the middle but it also has a cultural tourism attraction. Lake Sigombak Tourism Management cannot be separated from the lack of coordination from related stakeholders, so that the development plan and management of Lake Sigombak tourism cannot be carried out properly, it is necessary to conduct research on Feasibility Analysis of Ecotourism for Lake Sigombak Nature Tourism. This type of research is descriptive qualitative which was conducted for one month, in Teluk Kembang Jambu Village, Tebo Regency. Data collection techniques were carried out by direct observation, interviews, and documentation. The sample of this research is the visitors of Lake Sigombak Nature Tourism taken by using the Accidental Sampling method. Data analysis used descriptive qualitative techniques. Based on the results of research based on ODTWA, the Lake Sigombak Nature Tourism Area got an average index value of 64.64% of the average overall criteria. Attractiveness gets a score of 64.15%. Accessibility scored 67.86%, accommodation 33.33%, supporting facilities and infrastructure 87.93%, conditions around the area scored 65.09%, water and environmental conditions 82.99%, and marketing 51.15%. Overall, the Lake Sigombak Ecotourism area is declared unfit for development, so there is still a lot that needs to be improved, seeing the tourism conditions found in the Lake Sigombak Nature Tourism area. Keywords: Ecotourism, Lake Sigombak Nature Tourism, Natural Tourism Attractions (NTA).   ABSTRAK Ekowisata adalah perjalanan wisata ke wilayah-wilayah yang lingkungan alamnya masih asli dengan menghargai warisan budaya dan alamnya. Wisata Alam Danau Sigombak terletak di Desa Teluk Kembang, Jambu, Kabupaten Tebo, dan memiliki daya tarik wisata alam berbentuk Danau dengan Pulau ditengahnya selain itu juga memiliki daya tarik Wisata Budaya. Pengelolaan Wisata Danau Sigombak tak lepas dari kurangnya kordinasi dari stake holder terkait, sehingga rencana pembangunan dan pengelolaan wisata Danau Sigombak tidak mampu terlaksana dengan baik, maka perlu dilakukan penelitian mengenai Analisis Kelayakan Ekowisata Wisata Alam Danau Sigombak. Jenis penelitian ini adalah Kualitatif Deskriftif yang dilakukan selama satu bulan, di Desa Teluk Kembang Jambu, Kabupaten Tebo. Teknik pengambilan data dilakukan dengan Observasi secara Langsung, Wawancara, dan Dokumentasi. Sampel penelitian ini adalah pengunjung Wisata Alam Danau Sigombak yang diambil dengan menggunakan metode Accidental Sampling. Analisis data menggunakan teknik kualitatif deskriftif. Berdasarkan hasil penelitian yang berpedoman pada ODTWA, Kawasan Wisata Alam Danau Sigombak mendapatkan nilai indeks rata rata 64,64% dari rata rata keseluruhan kriteria. Daya tarik mendapatkan nilai sebesar 64,15%. Aksesibilitas mendapatkan nilai sebesar 67,86%, Akomodasi sebesar 33,33%, sarana dan prasarana penunjang sebesar 87,93%, kondisi sekitar kawasan mendapatkan nilai sebesar 65.09%, kondisi air dan lingkungan sebesar 82.99%, dan pemasaran mendapatkan nilai sebesar 51.15%. Secara keseluruhan kawasan Ekowisata Danau Sigombak dinyatakan belum layak dikembangkan, sehingga masih sangat banyak yang perlu diberbaiki, melihat kondisi Wisata yang ditemukan di kawasan Wisata Alam Danau Sigombak. Kata kunci: Ekowisata, Obyek Daya Tarik Wisata Alam (ODTWA), Wisata Alam Danau Sigombak